Preliminary Study of Formic Acid Synthesis from Biomass - Tedi Hudaya; Felicia Kristianti; Tatang Hernas Soerawidjaja (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2016)
Hydrogen is considered as one of the energy sources can provide emission-free application. However, one of the difficulties of using hydrogen is the coherent characteristic of hydrogen, that obstruct the efficient and safe storage of the hydrogen. Therefore concepts for the liquid phase storage under ambient condition using formic acid have received many attention, so that formic acid synthesis methods that is economically feasible and enviromentally friendly is need to be known. One of them is oxidation sorbitol to form formic acids. This research will begin with synthesis of H5PV2Mo10O40 as catalyst. Preliminary experiments is done by varying reaction time (15,20, 25, 30, 60, 120, 180 minutes) to get the most favorable time. The main experiments will be done by varying pressure, temperature, and the catalyst’s in the exact reaction time. All of the oxidation reaction product then is analyzed using HPLC. The results show that the conversion of sorbitol is usually achieved at almost 100%, and the maximum yield that is achieved (75,40%) at 25 bar, 1400C, and 0,6% w/w. The effects of temperature to conversion of sorbitol and yield of formic acid is significant. The effect pressure to conversion and yield is significant at 1200C, but slightly unsignificant at the other variation. The effects of catalyst concentration is unsignificant to conversion of sorbitol, but is significant to the yield of formic acid